Pengoptimalisasian Pemasaran Kerajinan Tangan Desa Pendem - Salman Salman; Emmy Dyah Setyowati; M. Alvin Maulana; Sri Ayu Dwi Santika (Universitas Mataram, 2021)
Handicrafts from Pendem Village, Central Lombok Regency, West Nusa Tenggara, from an economic perspective, especially marketing, have not been maximized due to a number of obstacles. Therefore, the team for the KKN Thematic (Community Service Program) Unram took the initiative to optimize the marketing of Pendem Village handicrafts. The method used is to conduct online marketing guidance for their craft products. As a result, the partners were very enthusiastic and together with the KKN Unram team carried out online marketing activities.